Pharmaco therapy of neonates - Kushairi, Siti Sarah Syahirah; Ibrahim, Norkasihan (Faculty of Pharmacy, 2026)
When dealing with neonatal patients, defined as newborn infants ≤ 28 days of life, it is important not to simply regard them as younger children, whose doses of drugs can be adjusted based only on body weight. Neonates have distinct physiological and developmental characteristics that significantly influence drug response. Therefore, many pharmacological factors must be considered when prescribing and monitoring medications in this population.